Pregnancy in case of exstrophy of bladder - Amin, Kinnari Vilaschandra; Tiwari, Namrata; Goel, Anchal; Chauhan, Anahita R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Bladder exstrophy or ectopia vesica is an unusual congenital anomaly which exists in the spectrum of the exstrophy- epispadias complex. It most commonly involves protrusion of the urinary bladder due to defect in the lower abdominal wall. It has variable presentation and often includes abnormalities of the pelvic floor, bony pelvis and genitalia. Patients undertaking pregnancy after surgical repair of such an anomaly are rare. Planned Cesarean section at term is considered the appropriate mode of delivery. We present a case of 21-year-old patient who had uneventful preterm vaginal delivery following surgical repair of bladder exstrophy in childhood.